Thoracic Spondylolisthesis that Worsened Symptoms of the Thoracic Spinal Cord Potentially Caused by Patient Positioning During Surgery: A Case Report - , Minoru Hoshimaru, Hiroaki Manabe, Miyuki Fukuda, Shigeo Ueda, Tomoaki Fujita, Nobuhiro Sasaki, Masayuki Kuroda (International Journal of Innovative Research in Medical Science, 2017)
Thoracic spondylolisthesis is a rare disease, but symptoms become severe once a patient develops myelopathy. We experienced a case of thoracic spondylotic myelopathy caused by mild degree of spondylolisthesis in the upper thoracic spine associated with cervical and lumbar spine lesions. The symptoms worsened after prone positioned cervical decompression. Dynamic computed tomography imaging of the thoracic spine in forward and backward bending was useful in evaluating instability of the thoracic spine. Because the caudal part of the region causing spondylolisthesis had fused with the anterior longitudinal ligament, regional instability potentially occurred based on the principle of lever arm even though the degree of spondylolisthesis was mild. Diagnosis of thoracic spondylolisthesis is difficult, but because symptoms are likely to become severe, it is necessary to carefully acknowledge pathological conditions.